DEMAND AND SUPPLY OF MILENIAL LABOR AND WAGES: THEORIES AND SOME PORTRAITS IN INDONESIA - Yuannisa, Rizka Adlia; Yuni, Ika Darma; Nasution, Rizka; Harahap, Isnaini (Proceeding International Seminar of Islamic Studies, 2023)
The labor issue is a very complex and big problem. Good working conditions, high output quality, decent wages and the quality of human resources are issues that always arise in discussions about the workforce in addition to issues of industrial relations between workers and the business world. It can be said that employment in Indonesia is still facing several imbalances, both structural and sectoral. then one of the targets that need to be pursued is to increase the efficiency of the workforce. The demand for labor, which is affected by the marginal value of the product (Value of Marginal Product, VMP), the supply of labor, which is influenced by the free working hours of individual workers and wages, theoretically must be considered so that the policies implemented are close to the desired goals.